ANALISIS PEMBIAYAAN PENDIDIKAN DASAR DAN PERMASALAHANNYA - Rizki Ananda; Ainun Nabila; Elfi Sarini; Kasih Febri Maharani; Rauda Tunnur; Wiwit Darmawita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Basic education is a crucial foundation for the development of quality human resources. In its implementation, financing becomes a critical factor that determines the success of basic education programs. This article aims to analyze the structure of basic education financing in Indonesia and identify various issues that still hinder its effectiveness and efficiency. This study uses a qualitative-descriptive approach based on literature review and secondary data from government reports. The analysis results show that although the government has allocated significant funds through various schemes such as the School Operational Assistance (BOS), challenges still exist in the distribution, effective utilization, and transparency of the budget. Policy reforms and strengthening governance capacity are needed to ensure the sustainability and quality of basic education.